Gender and labor market situation among technical university graduates in Poland - Michał Tomasz Tomczak (Jesuit University Ignatianum in Krakow, 2018)
RESEARCH OBJECTIVE: The aim of article is to analyse the professional situation of technical university graduates in Poland, focusing on the gender as the key impact factor. THE RESEARCH PROBLEM AND METHODS: The research problem was to examine the influence of gender on the employee's professional situation among technical university graduates in Poland. Empirical data was gained as a result of six annual quantitative research projects, conducted in the years 2012‑2017 on a total sample of almost 8000 respondents. THE PROCESS OF ARGUMENTATION: Firstly, the method of empirical research and hypotheses were described.Secondly, the relation of gender and the situation in the Polish labor market was presented and then the situation of technical university graduates within the contemporary labor marketwere outlined. Finally, there was a presentation of research results and summary with recommendations. RESEARCH RESULTS: The results confirm the influence of gender on the employee's professional situation, which is worse for women, also in the case of technical university graduates. Women fared worse than men i.a. in terms of the percentage of working individuals, the length of the period of searching for employment upon graduation and they were paid less than men. Nevertheless, it should be emphasized that the situation of both the women and the men surveyed can be described as favourable. CONCLUSIONS, INNOVATIONS, AND RECOMMENDATIONS: It can be hoped that the differences will be reduced. The changes should focus primarily on two key areas: the amount of remuneration received and the nature of the workplace.